Difficulties in diagnosing atypical hemolytic uremic syndrome - N. V. Fomina; L. D. Chesnokova; O. A. Konderova; S. A. Smakotina; E. V. Utkina; V. Yu. Isaev (Сибирский научный медицинский журнал)
The paper presents the case of clinical observation of a patient with atypical hemolytic-uremic syndrome (aHUS). aHUS is a disease characterized by an unfavorable prognosis (severe or catastrophic course with rapid development of terminal renal or multi-organ failure). The aim of the study is to evaluate the approaches to differential diagnosis of aHUS in clinical practice.Material and methods. The study was conducted on the basis of the Nephrology Department of Kemerovo Regional Clinical Hospital n.a. S.V Belyaev. The clinical observation of patient D., aged 26 years old, is discussed.Results and discussion. Diagnosing aHUS requires: 1) diagnosing thrombotic microangiopathy (TMA: thrombocytopenia or decrease in platelet count by more than 25 % of original, visceral damage (kidneys, CNS, gastrointestinal tract, heart, lungs)); 2) ruling out HUS associated with Shiga toxin-producing Escherichia coli (STEC-HUS; negative for Shiga-toxin in blood and stool), thrombotic thrombocytopenic purpura (TTP), systemic connective tissue disease, catastrophic antiphospholipid syndrome, HIV infection; 3) assessing the activity of ADAMTS13 (decrease confirms the aHUS diagnosis); 4) proving normal content of complement components C3 and C4 as an additional argument in favor of aHUS diagnosis. At the first stage, the patient was diagnosed with TMA (platelet content 37 x 109/l, hemoglobin content 59 g/l), LDH up to 824 E/l), liver damage (AST, ALT and LDH activity 55, 60 and 824 U/l, respectively), kidney damage (acute renal damage), lungs, heart, and brain damage. At the second stage the following diagnoses were ruled out: STEC-HUS (Shiga toxin in blood and stool was not detected), TTP (ADAMTS13 activity level was 66 %, whereas reference values are 93-113 %, in TTP - below 5-10 %); systemic connective tissue diseases catastrophic antiphospholipid syndrome, HIV infection sepsis. Normal values of C3 (0.9 g/l) and C4 (0.23 g/l) complement components did not rule out the diagnosis of aHUS.